Language proficiency and teacher knowledge bases in the teaching of science through English / Asiah Mohd Sharif - Asiah, Mohd Sharif (2013)
This study examines the teaching of science through English by primary teachers with limited English proficiency (LEP) following the implementation of a language of instruction policy (i.e. English for Teaching Mathematics and Science- ETeMS) in Malaysia. The study investigates the nature of talk by LEP teachers in the rural classroom and its impact on the teaching of science through English which is a form of content-based instruction (CBI). It also investigates the extent to which teacher knowledge bases influenced the language use of the LEP teachers in their delivery of science through English. The theoretical framework for this study is provided by Turner-Bisset (2001) and a case study approach is employed for data collection. Three LEP teachers in a rural primary setting tasked with teaching science through English provided data for analysis. Findings were culled from transcripts of nine lessons taught, observations, interviews, questionnaires and documents. The findings show that the teachers did have all the knowledge bases for teaching proposed by Turner-Bisset (2001) although the strengths varied. Proficiency in the medium of instruction emerged as the knowledge base that impacted the most on the successful/meaningful teaching and learning of science through English in the rural classroom. Limited English proficiency drove teachers to use their mother tongue (Malay) liberally; to use fragments or simplified structures of English; to rely on Malay grammar, resulting in inaccuracies in language use; and to resort to meaning-focused lessons which left errors uncorrected. Furthermore, limited proficiency in English prevented teachers from being creative in their language use and limited their questioning techniques which seemed to induce low level thinking on the part of students. The above inadequacies impeded their modelling role and greatly constrained their ability to fully realize the intentions of the new science curriculum. The iv pedagogical content knowledge that developed from the amalgamation of the different knowledge bases therefore was weak. The LEP teachers, on the whole, lacked knowledge in integrating content and language learning which is critical for the success of teaching science through English. It can be concluded that the LEP teachers were not empowered to meet the challenges of teaching science through English because they were not fully prepared for it. Compelling evidence from this study shows that language proficiency is a teacher knowledge base imperative for second language teachers tasked with CBI. Therefore, language proficiency, the researcher proposes, deserves inclusion in Turner-Bisset’s (2001) model of teacher knowledge bases. It can also be concluded that in order for teachers to succeed in the CBI classroom, they need to be trained in and be knowledgeable of ways to integrate language and content. Achieving well-prepared teachers for teaching science through English therefore should focus on continuous building of teachers’ knowledge in the applications of instructional strategies for integrating content and language.